Practical Theology from the Perspective of Catholic Spirituality: A Hermeneutic of Discernment - Lavallee, Marc Henri (International journal of practical theology, 2016)
This article examines practical theological hermeneutics through the lens of Catholic spirituality. Key to understanding the movement from description to analysis to revised praxis is the ways in which interpretive communities understand the connections between divine reality and human reality. In light of this, the article explores the relationship between epistemology and pneumatology found within Christian tradition by proposing an approach to practical theological hermeneutics rooted in the Ignatian practice of spiritual discernment. By doing so, this article seeks to contribute the potential contours of a distinctive Roman Catholic contribution to practical theology, and in a broader sense, show how the practice of discernment presents studies and methods in practical theology with a way of understanding connections among practical wisdom, habitus, research, and theological interpretation.